Development of an age‐adjusted model for blood neurofilament light chain. Issue 4 (1st March 2022) - Harp, Christopher; Thanei, Gian‐Andrea; Jia, Xiaoming; Kuhle, Jens; Leppert, David; Schaedelin, Sabine; Benkert, Pascal; von Büdingen, H‐Christian; Hendricks, Robert; Herman, Ann
Abstract: Objective: To develop an age‐adjustment model for neurofilament light chain (NfL), an emerging injury marker in patients with a range of neurologic conditions including multiple sclerosis (MS). Methods: Serum and plasma samples were collected from a healthy donor (HD) cohort of 118 individuals aged 24 to 66 years, 90 patients with relapsing MS (RMS) and 22 patients with progressive MS (PMS). Serum and plasma samples were assessed for NfL using the SIMOA assay (Quanterix NfL Advantage Kit™). A log‐linear model was used to evaluate the relationship between NfL and age and to calculate age‐adjusted NfL levels. Results: Higher serum and plasma NfL levels were significantly associated with increasing HD age. Log‐transformation of blood NfL levels reduced heteroscedasticity and skewness. A log‐linear model enabled adjustment for age‐related increase in serum and plasma NfL levels (2.3% [95% CI, 1.6–2.9] and 2.6% [95% CI, 1.3–3.3] per year, respectively). Following age adjustment, NfL did not show significant association with HD sex or ethnicity. While unadjusted serum NfL levels were elevated in patients with PMS (mean age 56 years) compared with those with RMS (mean age 37 years), age‐adjusted NfL levels did not differ. Interpretation: A log‐linear, age adjustment model was developed to enable comparison of NfL levels across populations with different ages. While additional data and evidence are needed for patient‐level adoption, this could be a valuable tool for interpreting NfL levels across a range of patient groups with neurologic conditions.